Brief history of distance education in Cuba and the world - Raúl López Fernández; Míriam Gutiérrez Escobar; Silvia Vázquez Cedeño; Mikhail Benet Rodríguez; Rachel Seijo Yanes; Alexander Cándido Hernández Petitón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Distance education has recently become a very useful educational practice due to the dynamics of today's world, the advances in the Information and Communication Technologies, as well as the need to achieve quality education overcoming distances and promoting personal growth and intellectual maturity of a growing number of people of all genres and latitudes. This paper aims to conduct a historical review of this type of education in Cuba and the world, from its origins to present times, for which a literature review was conducted covering different countries in Europe, Asia, Africa, America and Cuba, so that it can help all those who study this subject.